Characteristics and Clinical Features of Anorectal Malformations Without Fistula: A Systematic Literature Review - Azzahra Maghfirah Mustamin; Berry Erida Hasbi; Kartini Badruddin (HM Publisher, 2024)
Anorectal malformation (MA) without fistula is a form of congenital abnormality that is often found in newborn babies. This study aims to identify the characteristics and clinical features of MA without fistula based on the latest scientific evidence. A systematic search was conducted on the PubMed, Scopus, and Web of Science databases using relevant keywords. Inclusion criteria included observational studies reporting the characteristics and clinical features of MA without fistula in humans. Two independent researchers conducted study selection, data extraction, and study quality assessment using the JBI Critical Appraisal Checklist tool. A total of 25 studies (2018-2024) involving 1548 MA patients without fistula met the inclusion criteria. The majority of patients were male (62%). The average age at diagnosis is 2 days. The most frequently reported clinical symptoms were absence of anus (100%), abdominal distension (78%), and vomiting (65%). The most common classification of MA without fistula was perineal (45%), followed by vestibular (30%) and cloacal (25%). The most frequently performed definitive surgery was perineal anoplasty (55%), followed by posterior sagittal anorectoplasty (PSARP) (35%) and laparoscopic-assisted anorectoplasty (10%). The most frequently reported postoperative complications were anal stenosis (15%), surgical wound infection (10%), and rectal prolapse (5%). MA without fistula is more common in male babies. The main clinical symptoms are absence of anus, abdominal distension, and vomiting. The perineal classification is the most common. Perineal anoplasty is the most frequently performed definitive surgery. Post-operative complications that need to be watched out for are anal stenosis, surgical wound infection, and rectal prolapse.